Fundamental aspects of plasma chemical physics : kinetics /: kinetics. (2015) - Capitelli, M; Celiberto, Roberto; Colonna, Gianpiero; Esposito, Fabrizio; Gorse, Claudine; Hassouni, Khaled; Laricchiuta, Annarita; Longo, Savino
No abstract available